Adoption of Islamic Gold Savings (Cicil Emas) at Bank Syariah Indonesia: A Behavioral Finance Perspective - Nazwa Ananta Farliany; Ario Purdianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze how perceptions of value, trust, and religiosity influence the decision to open an Islamic Gold Savings account at the Siliwangi Cirebon Branch of Bank Syariah Indonesia (BSI). The study employed a quantitative approach with an associative design and involved 160 respondents selected through purposive sampling. The research indicates that perceptions of values and trust significantly and positively influence the adoption of Islamic Gold Savings. Validity and reliability tests, classical assumption tests, and multiple linear regression with t- and F-tests were used to analyze the data using SPSS, while religiosity had a negative effect, indicating that highly religious customers tend to prefer the product. In general, economic principles, institutional beliefs, and religious factors influence the decision to adopt the product.